Sarcoporosis is a part of aging - Broulík, Petr (Prague Medical Report, 2019)
Ageing is associated with the accumulation of damage to all the macromolecules within and outside cells leading to progressively more cellular and tissue defects and resulting in age-related frailty, disability and disease. As a result of the aging process the bone deteriorates in composition, structure and function. Age-related musculoskeletal losses are a major public health burden because they can cause physical disability and increased mortality. We tried to find out on a small set of old women, without risk factors for osteoporosis, what caused them the loss of bone minerals. All 492 women had just only one risk factor - the old age. Laboratory findings have shown a decreased serum C telopeptide and low serum alkaline phosphatase circulating markers, used to quantify bone resorption and formation, and very low level of vitamin D. Very low level of vitamin D that disrupted calcium absorption through the intestine, and decreased calcemia increased parathyroid hormone levels with resulting bone effect. The manifestation of physiological aging is worsening eyesight, peripheral neuropathy, depression, worsening of physical condition, skin aging, sarcopenia and bone mineral loss. Senile osteoporosis, which is not caused by known risk factors for osteoporosis, does not appear to be a separate disease, but is part of the physiological process of aging. Treatment of senile osteoporosis should be focused on the control of secondary hyperparathyroidism by administration of vitamin D and calcium. The risk of fractures in the advanced age is determined by a large number of factors ranging from hazards in the home environment to frailty and poor balance.
Keywords: osteogeneze; kostní denzita; parathormon; Osteoporosis; Collagen Type I; Humans; Female; Aging; Osteogenesis; lidé; Alkaline Phosphatase; Bone Density; vitamin D; Peptides; ženské pohlaví; Vitamin D; peptidy; osteoporóza; kolagen typu I; vápník; Calcium; Parathyroid Hormone; alkalická fosfatasa; stárnutí